Real stories of Christian initiation : lessons for and from the RCIA - Yamane, David; MacMillen, Sarah; Culver, Kelly (Collegeville, Minn. : Liturgical Press, 2006)
"Relates real experiences from parishes that have used the Rite of Christian Initiation of Adults in the Roman Catholic Church; draws lessons for the church from these experiences"--Provided by publisher.
St. Mary's : "we're about making disciples" -- St. Mark's : "faithful to the past" -- St. Innocent : "only just the beginning" -- St. John Bosco : task-completion initiation and "experience" -- Queen of Peace : "come and follow me".
Includes bibliographical references (p. 135-137) and index.
Keywords: Catholic Church; Catholic Church -- United States -- Membership -- Case studies; Initiation rites -- Religious aspects -- Catholic Church -- Case studies